A microRNA circuit mediates Transforming Growth Factor-ß1 autoregulation in renal glomerular mesangial cells - Kato, Mitsuo (2011)
Enhanced transforming growth factor-β1 (TGF-β1) expression in renal cells promotes fibrosis and hypertrophy during the progression of diabetic nephropathy. The TGF-β1 promoter is positively controlled by the E-box regulators, Upstream Stimulatory Factors (USFs), in response to diabetic (high glucose) conditions; however, it is not clear whether TGF-β1 is autoregulated by itself. Since changes in microRNAs (miRNAs) have been implicated in kidney disease, we tested their involvement in this process. TGF-β1 levels were found to be upregulated by microRNA-192 (miR-192) or miR-200b/c in mouse mesangial cells. Amounts of miR-200b/c were increased in glomeruli from type 1 (streptozotocin) and type 2 (db/db) diabetic mice, and in mouse mesangial cells treated with TGF-β1 in vitro. Levels of miR-200b/c were also upregulated by miR-192 in the mesangial cells, suggesting that miR-200b/c are downstream of miR-192. Activity of the TGF-β1 promoter was upregulated by TGF-β1 or miR-192, demonstrating that the miR-192-miR-200 cascade induces TGF-β1 expression. TGF-β1 increased the occupancy of activators USF1 and Tfe3, and decreased that of the repressor Zeb1 on the TGF-β1 promoter E-box binding sites. Inhibitors of miR-192 decreased the expression of miR-200b/c, Col1a2, Col4a1 and TGF-β1 in mouse mesangial cells, and in mouse kidney cortex. Thus, miRNA-regulated circuits may amplify TGF-β1 signaling accelerating chronic fibrotic diseases such as diabetic nephropathy.